2013
DOI: 10.1155/2013/919374
|View full text |Cite
|
Sign up to set email alerts
|

Antiosteoclastic Activity of Milk Thistle Extract after Ovariectomy to Suppress Estrogen Deficiency-Induced Osteoporosis

Abstract: Bone integrity abnormality and imbalance between bone formation by osteoblasts and bone resorption by osteoclasts are known to result in metabolic bone diseases such as osteoporosis. Silymarin-rich milk thistle extract (MTE) and its component silibinin enhanced alkaline phosphatase activity of osteoblasts but reduced tartrate-resistant acid phosphatase (TRAP) activity of osteoclasts. The osteoprotective effects of MTE were comparable to those of estrogenic isoflavone. Low-dose combination of MTE and isoflavone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 29 publications
1
19
0
Order By: Relevance
“…Moreover, the combination of silymarin with lignin showed a more potent, synergistic effect in suppressing intestinal tumorigenesis [155]. Interestingly, other ER-related effects of silymarin in vivo are improved endothelial dysfunction, which could prevent cardiovascular diseases in menopause [156], and antiosteoporotic activity in ovariectomized rats, but these are associated with a mild increase in uterine weight [157158]. In a rat model of Parkinson’s disease, silymarin exerted a neuroprotective effect, which appears to be ER mediated because it was partially reversed by fulvestrant administration [159].…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 99%
“…Moreover, the combination of silymarin with lignin showed a more potent, synergistic effect in suppressing intestinal tumorigenesis [155]. Interestingly, other ER-related effects of silymarin in vivo are improved endothelial dysfunction, which could prevent cardiovascular diseases in menopause [156], and antiosteoporotic activity in ovariectomized rats, but these are associated with a mild increase in uterine weight [157158]. In a rat model of Parkinson’s disease, silymarin exerted a neuroprotective effect, which appears to be ER mediated because it was partially reversed by fulvestrant administration [159].…”
Section: Update On Chemical Classes Comprising Erα and Erβ Modulatorsmentioning
confidence: 99%
“…In addition to label indications, many studies have reported the beneficial effects of silymarin for the treatment of several diseases (Fig. ), including sepsis (Kang et al ., ; Toklu et al ., ), burns (Toklu et al ., ), osteoporosis (Kim et al, ; Mohd Fozi et al ., ), arthritis (Gupta et al ., ), hypercholesterolemia (Krecman et al, ; Skottova and Krecman, ), cancer (Singh et al, ; Bosch‐Barrera and Menendez, ; Scavo et al, ; Yurtcu et al, ), viral infections (Lani et al, ), diabetes (Malekinejad et al , ; Soto et al , ; Zhang et al , ; Ebrahimpour Koujan et al , ), Alzheimer's disease (Duan et al, ; Kumar et al, ), and Parkinson's disease (Haddadi et al, ; Lee et al, ). Silymarin treatment likewise attenuated the severity of radiotherapy‐induced mucositis in a clinical trial (Elyasi et al , ).…”
Section: Silymarinmentioning
confidence: 99%
“…These pharmacological effects are attributed due to its strong antioxidant activity. [13][14][15][16][17] In this study, we evaluated the toxic effect of lead acetate on the kidneys and blood of rats based on histopathological alterations and DNA damage. We also evaluated the protective effect of silymarin and DMSA either individually or in combination against Pb toxicity.…”
Section: Introductionmentioning
confidence: 99%